2019
DOI: 10.3389/fphys.2019.00007
|View full text |Cite
|
Sign up to set email alerts
|

Annexin II Light Chain p11 Interacts With ENaC to Increase Functional Activity at the Membrane

Abstract: The epithelial Na+ channel (ENaC) provides for Na+ absorption in various types of epithelia including the kidney, lung, and colon where ENaC is localized to the apical membrane to enable Na+ entry into the cell. The degree of Na+ entry via ENaC largely depends on the number of active channels localized to the cell membrane, and is tightly controlled by interactions with ubiquitin ligases, kinases, and G-proteins. While regulation of ENaC endocytosis has been well-studied, relatively little is understood of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…marginatum , and Hya. anatolicum were collected from humans (farmers and the general public) [ 69 ], highlighting the importance of better managing human-tick interactions in this region. The current study has reported several tick bites in home-based livestock settings, noting that most were simply ignored, which may represent an important public health concern for zoonotic transmission of TBDs.…”
Section: Discussionmentioning
confidence: 99%
“…marginatum , and Hya. anatolicum were collected from humans (farmers and the general public) [ 69 ], highlighting the importance of better managing human-tick interactions in this region. The current study has reported several tick bites in home-based livestock settings, noting that most were simply ignored, which may represent an important public health concern for zoonotic transmission of TBDs.…”
Section: Discussionmentioning
confidence: 99%
“…The roles for p11 in regulating ASIC1a functions in living animals remain to be delineated. p11 Increases Cell Surface Levels of Epithelial Na + Channel (ENaC) and Promotes Na + Absorption It has more recently been demonstrated that p11 binds ENaCs and regulates an exocytic pathway for these channels to the cell surface [35]. In vitro binding assay showed that p11 directly p11 retains TWIK-related acid sensitive K + channel-1 (TASK-1) channels in the endoplasmic reticulum, but increases cell surface levels of NaV1.8, acid-sensing ion channel-1 (ASIC-1), and epithelial Na + channel (ENaC).…”
Section: P11 Regulates a Diverse Set Of Ion Channelsmentioning
confidence: 99%
“…Annexin II light chain p11, a member of the S100 family of small and dimeric EF-hand Ca 2+ -binding proteins, has been demonstrated to control the number of ENaCs present in the membrane via the exocytic pathway (Cheung et al, 2019). Considering that ASICs and ENaCs are both members of the DEG/ENaC gene family (Boscardin et al, 2016), it is rational to assume that p11 may have a regulatory effect on ASICs.…”
Section: Effector Proteinsmentioning
confidence: 99%